2016
DOI: 10.1038/srep36698
|View full text |Cite
|
Sign up to set email alerts
|

Rescue therapy with Tanshinone IIA hinders transition of acute kidney injury to chronic kidney disease via targeting GSK3β

Abstract: Acute kidney injury (AKI) remains challenging for clinical practice and poses a risk of developing progressive chronic kidney disease (CKD) with no definitive treatment available yet. Tanshinone IIA, an active ingredient of Chinese herbal Salvia miltiorrhiza, has been widely used in Asia for the remarkable organoprotective activities. Its effect on established AKI, however, remains unknown. In mice with folic acid-induced AKI, delayed treatment with Tanshinone IIA, commenced early or late after injury, diminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 67 publications
2
28
0
Order By: Relevance
“…As a key component of S. miltiorrhiza, TSIIA has been used to treat multiple diseases, including Alzheimer's disease, chronic kidney disease, cerebral ischemic injury and DCM (23)(24)(25)(26). Furthermore, previous studies have demonstrated that TSIIA could attenuate myocardial ischemia reperfusion injury due to its antioxidant capacity (27).…”
Section: Discussionmentioning
confidence: 99%
“…As a key component of S. miltiorrhiza, TSIIA has been used to treat multiple diseases, including Alzheimer's disease, chronic kidney disease, cerebral ischemic injury and DCM (23)(24)(25)(26). Furthermore, previous studies have demonstrated that TSIIA could attenuate myocardial ischemia reperfusion injury due to its antioxidant capacity (27).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the magnesium lithospermate B isolated from SM had inhibitory effects on urine protein excretion, blood urine nitrogen, mesangial proliferation, tubule-interstitial lesion, and glomerular sclerotic change in nephrectomized rats ( Yokozawa et al, 1995 ). Another major compound, tanshinone IIA, inhibited over-activity of glycogen synthase kinase 3β to protect transition of kidney injury from acute to chronic changes ( Jiang et al, 2016 ). AM is one of the most important herbs to tonify Qi.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of reports demonstrated Tan has been used for the treatment of multiple diseases, including cardiovascular disease [ 11 ], cerebral ischemia [ 12 ] and bone diseases such as osteoporosis [ 13 ]. In kidney disease, Tan not only protects against acute kidney injury [ 14 , 15 ], but also has protective effects on chronic kidney disease, including uric acid nephropathy [ 16 ], doxorubicin induced nephropathy [ 17 ], 5/6 nephrectomy induced chronic kidney disease [ 18 ] and hypothermic kidney preservation [ 19 ]. Although Kim et al [ 20 ] demonstrated that Tan exerted protective effect on the early stage of diabetic nephropathy in animal model, the mechanisms remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%